Newt Opportunities for Understanding the Dedifferentiation Process - Ziad Y. Chaar; Catherine Tsilfidis (The Scientific World Journal)
Urodele amphibians, such as the newt Notophthalmus viridescens, have the unique ability to regenerate limbs, spinal cord, eye structures, and many vital organs through a process called epimorphic regeneration. Although the cellular basis of regeneration has been studied in detail, we know relatively little about the molecular controls of the process. This review provides an overview of forelimb regeneration in the newt, addressing what we know about cellular and molecular aspects. Particular focus is placed on the dedifferentiation process, which yields a population of embryonic-like pluripotent cells that will eventually reform the lost structure. This cellular plasticity seems to be the key to regenerative ability. We discuss the dedifferentiation process in newt forelimb regeneration and outline the various studies that have revealed that mammalian cells also have the ability to dedifferentiate if given the appropriate triggers.